2013
DOI: 10.1007/s00464-013-2939-y
|View full text |Cite
|
Sign up to set email alerts
|

Biologic meshes are not superior to synthetic meshes in ventral hernia repair: an experimental study with long-term follow-up evaluation

Abstract: Parietex composite mesh demonstrated the best long-term results compared with all the other meshes. The biologic non-cross-linked mesh, Strattice, showed little adhesion formation and moderate shrinkage but poor incorporation. Biologic meshes are promising, but varying results require a more detailed investigation and demonstrate that biologic meshes are not necessarily superior to synthetic meshes. The significant changes that take place between 30 and 90 days should lead to careful interpretation of short-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…Although biological meshes are routinely used in infected fields, their high costs remain a barrier to widespread use (43). In addition, there is insufficient evidence in the literature regarding the advantages of biologic meshes over synthetic meshes in hernia repair (44)(45)(46).…”
Section: Classes Of Meshmentioning
confidence: 99%
See 1 more Smart Citation
“…Although biological meshes are routinely used in infected fields, their high costs remain a barrier to widespread use (43). In addition, there is insufficient evidence in the literature regarding the advantages of biologic meshes over synthetic meshes in hernia repair (44)(45)(46).…”
Section: Classes Of Meshmentioning
confidence: 99%
“…Fundamentally, recurrence is caused by early degradation of the mesh, early removal of the mesh (as necessary following infections) or mesh failure ( Figure 5) (34,45,106). Mesh failure is caused by central mesh failure (mesh fracture) (60)(61)(62)(63) or fixation/suture line failure (107).…”
Section: Complications Hernia Recurrence/infectionmentioning
confidence: 99%
“…Mesh products that are able to induce mesothelial cell deposition are able to avoid production of multiple adhesions; biologic mesh products have demonstrated better mesothelial cell deposition than synthetic products. 8,9 While all mesh materials are known to produce adhesions, multiple studies have demonstrated decreased adhesion formation and better tissue integration of biologic mesh products as compared to synthetic mesh products. [9][10][11][12] The revascularization potential of biologic mesh is thought to promote access of host immune cells thereby providing further resistance to persistent infection.…”
Section: Biologic Meshmentioning
confidence: 99%
“…8,9 While all mesh materials are known to produce adhesions, multiple studies have demonstrated decreased adhesion formation and better tissue integration of biologic mesh products as compared to synthetic mesh products. [9][10][11][12] The revascularization potential of biologic mesh is thought to promote access of host immune cells thereby providing further resistance to persistent infection. This "proinflammatory" property of biologic mesh may prove superior at clearing infections and retarding the progress of biofilm to fulminant infection in the setting of contaminated fields.…”
Section: Biologic Meshmentioning
confidence: 99%
See 1 more Smart Citation